An Age‐Friendly Health System. Issue 3 (4th December 2020) - Lundy, Janice; Hayden, Deborah; Pyland, Stephanie; Berg‐Weger, Marla; Malmstrom, Theodore K.; Morley, John E.
Abstract : BACKGROUND/OBJECTIVES: To describe a screening and intervention program for geriatric syndromes instituted at a rural healthcare system that utilizes the 4Ms of an age‐friendly health system, and to provide exercise and cognitive stimulation therapy (CST) as part of an age‐friendly health program. DESIGN: Retrospective evaluation of clinical data. SETTING: Rural primary healthcare system. PARTICIPANTS: Older adults aged 65 years and older in Perry County, Missouri. MEASUREMENTS: Screening for geriatric syndromes was done using the Rapid Geriatric Assessment (RGA), which includes the FRAIL, SARC‐F, Simplified Nutritional Appetite Questionnaire (SNAQ), and Rapid Cognitive Screen (RCS). Outcomes for exercise and CST included the Five Times Sit to Stand (FTSS) and Timed Up and Go (TUG) tests, Cornell Scale for Depression in Dementia (CSDD), Saint Louis University Mental Status Examination (SLUMS), and Quality of Life in Alzheimer's Disease (QoL‐AD) measures. RESULTS: The RGA was administered to 1, 326 individuals of which 36.5% were frail, 42.1% were sarcopenic, 26.1% were at risk for anorexia, and 20.8% had dementia. Of these receiving exercise therapy, both the FTSS and the TUG were improved at 3 months and 12 to 24 months. In the CST group, SLUMS, QoL‐AD, and CSDD were improved at 7 weeks and 6 to 12 months. CONCLUSION: It is feasible to introduce a screening program for geriatric syndromes and respond to the results with successful exercise and cognitive stimulation therapy programs.